Pengembangan Perangkat Pembelajaran Muatan Lokal dengan Pembelajaran Blended Learning Berbasis Budaya Maluku untuk Meningkatkan Keterampilan Hidup Abad 21 - Leasa, Marleny; Arnold Sahalessy; John Rafafy Batlolona (Jurnal Pendidikan Indonesia, 2025)
Learning based on local wisdom needs to continue to be encouraged because it accommodates a contextual approach and preserves the cultural heritage of Indonesia, especially Maluku. The aim of this research is to develop local content learning tools with blended learning based on local wisdom to empower high school students' 21st century life skills. This research uses the Research and Development (R&D) model developed by Borg & Gall which consists of 10 stages. Sampling was carried out by random sampling, especially for schools that were declared participating after a placement test was carried out. The sample for the quasi experiment was class X high school students spread across 10 high schools, while the test subjects in the development stage used four high schools. Based on the results of research and valorization, it was found that the learning product had met product suitability standards, namely (Valid or can be used with minor revisions) through product validity testing by experts and field trials. The validation results are then revised until they meet the expected standards and then revalidation is carried out to ensure that the development product is valid and can be used for learning purposes, especially at the experimental research stage. The low percentage of research based on local wisdom with blended learning needs to be followed up by increasing this research with varied designs, measured variables, research subjects, and improving research locations. The implications of this research can contribute to improving the quality of more contextual learning, by integrating local cultural values in the teaching and learning process.